Inverse System in The Category of Intuitionistic Fuzzy Soft Modules - Abdullayev, S. E.; Bayramov, Sadi (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
This paper begins with the basic concepts of soft module. Later, we introduce inverse system in the category of intutionistic fuzzy soft modules and prove that its limit exists in this category. Generally, limit of inverse system of exact sequences of intutionistic fuzzy soft modules is not exact. Then we define the notion which is first derived functor of the inverse limit functor. Finally, using methods of homology algebra, we prove that the inverse system limit of exact sequence of intutionistic fuzzy soft modules is exact.